Pengembangan Aplikasi Point of Sales Berbasis Web pada Bengkel Menggunakan Metode Agile - Kurnia Naradinata; Afiani Agus Abdillah; Kahfi Ahmad Arpiandi (CV. Multi Kreasi Media, 2026)
Micro, Small and Medium Enterprises (MSMEs) in the automotive sector, such as repair shops, still heavily rely on manual transaction and stock recording, which is prone to data loss, calculation errors, and delayed reports. This study aims to design and implement a web-based Point of Sale (POS) application at G Speed Bintaro Workshop using the Agile method with the Scrum framework. The system implementation is built utilizing modern database technology and an appropriate development environment. The test results show that all features function according to specifications, including recording spare parts sales transactions and service services, automatic stock management, tracking customer vehicle medical history, and real-time operational reporting. This system is proven to mitigate vulnerabilities in transaction work document management, reduce queue buildup, and maintain strict inventory data synchronization. The application of a web-based POS application using the Agile method is an effective digitalization solution for automotive MSMEs.